Fenomena Kotak Kosong Dalam Pilkada Tahun 2024 - Mulyadi, Dedi; Simbolon, Cindy Claudia; Baidhowi, Nayla Ratu; Januwati, Pusfa; Lananda, Ardelia; Rahmah, Mila Arastasya (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
The implementation of regional head elections (Pilkada) in Indonesia faces various challenges, including the phenomenon of empty boxes that reflect public dissatisfaction with the candidates nominated. In the context of democracy, Pilkada should be a means for the people to express their sovereignty. However, the issue of the threshold and the practice of